Correlation of short form-36, energy expenditure and six-minute walk test in post coronary artery bypass graft and post percutaneous coronary intervention patients - Watesinee Kaewkhuntee (2018)
© 2015, Medical Association of Thailand. All rights reserved. Objective: To investigate the correlation between Short Form-36 (SF-36) and exercise capacity including: 1) metabolic equivalents measured by an exercise stress test (METs of EST), 2) peak oxygen consumption (VO2 peak), and 3) walking distances measured by a six-minute walk test (6MWT). Material and Method: SF-36, EST and 6MWT were estimated at the sixth week after coronary artery bypass graft (n = 17) and percutaneous coronary intervention (n = 13) patients. Pearson’s product-moment correlation was used to evaluate the relationship of parameters. Results: Physical functioning scale of SF-36 showed moderate correlation with METs (r = 0.55, p<0.01), fair correlation with VO2 peak of 6MWT (r = 0.46, p<0.05) and walking distance (r = 0.43, p<0.05). Bodily pain showed fair correlation with METs (r = 0.40, p<0.05) and walking distance (r = 0.45, p<0.05). Social functioning showed fair correlation with METs (r = 0.38, p<0.05). Report-health transition showed fair correlation with METs (r = 0.38, p<0.05) and walking distance (r = 0.41, p<0.05). Conclusion: The physical domain of SF-36 that comprised physical function, role-physical, bodily pain and general health correlated with physical capacity of these post-operation groups (r = 0.49, p<0.001). Therefore, clinicians can use the SF-36 and 6MWT to evaluate functional capacity in addition to EST and indirect calorimetry conveniently.